Tax reforms and fiscal shock smoothing - Amaglobeli, David (IMF working paper ;, 2019)
This paper examines the role of tax policy reforms in enhancing fiscal shock smoothing in a panel of 13 OECD economies during the period 1980-2017. The results suggest that tax reforms, in particular those that broaden the tax base, significantly enhance the ability of fiscal policy to mitigate the impact of growth shocks on disposable income. We find that the magnitude of shock smoothing increases from an average of 2 percent to 3-3½ percent following the reform. The effects are considerably higher for tax base than tax rate changes, and also higher for indirect tax than direct tax changes. The effects are symmetric-that is, the increase in shock smoothing following a reform expanding the tax base (rate) is similar to the decline in shock smoothing after a reform narrowing the tax base (rate). Tax elasticity, collection efficiency, and the progressivity of the tax system are important channels through which tax reforms affect fiscal stabilization.